Dynamics of the Formation of a Rotating Orbital Tether System with the Help of Electro-thruster. (2017) - Zabolotnov, Yu. M.
Abstract: The dynamics of the process of forming the rotating orbital tether system, which is a bundle of two small satellites, is analyzed. The cases of transition deployed tether system in rotation by means of two electric jet engines located on the end bodies are considered. Engines together form a pair of forces required sign, the control program includes active and passive portions of the motion system. Satellites are material points whose masses are comparable in magnitude, and the tether is weightless. The control program is formed by a relatively simple model in the mobile orbital coordinate system in the case of inextensible tether. The elongation effect of the tether, which leads to its eventual sagging is analyzed by a more complete model in a fixed geocentric coordinate system.